Force Reduction of Circular Cylinder using Square Disturbance Body at 600 Angle by 2D Numerical Simulation Unsteady-RANS - Putra, Meiki Eru; Rina, Rina; Nofriyandi, R; Sumiati, Ruzita (-)
Drag is an aerodynamic force that appears when the flow past the bluff body circular cylinder. Drag strongly influenced by the flow separation point. One of the ways reducing the drag force that is to control the flow by placing the disturbance body on the upstream side at a certain angle. Previous research has found at 60Âº angle of flow separation is faster than a single cylinder that produced greater drag. Therefore, this research was conducted to reduce the drag force on the corner with disturbance dimension variation. This research was carried out numerically using a FLUENT 6.3.26 CFD software in 2D unsteady viscous-RANS models Turbulence Model-Shear-Stress Transport (SST) k-Ï in a narrow channel. The geometry is simulated in a circular cylinder as the main body and the square cylinder as a disturbance body being placed in front of the main body by 0.16 s/D ratio. Dimensions of disturbance body varied at (s) 0,1; 0,2; 0,3; 0,4 dan 0,5 mm with a gap (Î´=0,4mm). Reynolds number based on the diameter of the cylinder, ie ReD 2,32x104. The simulation results show that the transition flow on shifting 60Âº SDB angle for all SDB dimensional variations do not produce turbulent. The best of drag force reduction in this configuration occurs on a cylinder at 0.2 mm disturbance dimensions is 48%.